Examining the Role of Newspapers in Promoting Public Awareness of Sustainable Development Goals: A Case of Habari Leo and Mwananchi - Ahmad Said Mohamedi,; Kaanaeli Kaale, (Technium Social Sciences Journal, 2026)
This study investigated the role of newspapers in raising public awareness of the Sustainable Development Goals (SDGs), focusing on Habari Leo and Mwananchi. A mixed-methods approach was utilized, integrating quantitative content analysis with qualitative thematic analysis to assess the extent and nature of SDG coverage, identify dominant themes, and capture readers’ perceptions through article review and survey data. Results showed that in 2020, Habari Leo and Mwananchi published a total of 647 articles and 337 photographs pertaining to the SDGs. Coverage was predominantly centered on social goals—especially Goal 2 (Zero Hunger), Goal 3 (Good Health and Well-being), Goal 4 (Quality Education), and Goal 5 (Gender Equality)—while economic and environmental goals received limited attention, with some entirely overlooked. Thematic analysis indicated that 54% of articles were informational, 23% addressed implementation, 7% provided analytical perspectives, and only 2% focused on project evaluation. Reader surveys revealed that 60% rated the coverage as ordinary and 40% as below average, with widespread calls for more comprehensive and in-depth reporting. The study highlights significant imbalances and a lack of depth in SDG coverage by Tanzanian newspapers, underscoring the need for more analytical and evaluative journalism. These findings contribute to media and communication theory by exposing gaps in SDG reporting and offer policy and practical recommendations for Tanzanian media to strengthen their coverage, thereby advancing both national and global development objectives.